Synoptic patterns associated with high-frequency sea level extremes in the Adriatic Sea - K. Ruić; J. Šepić; M. Vojković (Ocean Science)
This study focuses on the classification of synoptic conditions leading to episodes of extreme high-frequency (HF) sea level oscillations in the Adriatic Sea (Mediterranean). Two types of extreme episodes were obtained from sea level time series measured at six tide gauge stations: (i) HF extremes, extracted from HF components (periods shorter than 2 h) of sea level time series and defined as periods in which the HF component was above a threshold value, and (ii) compound extremes, extracted from residual (de-tided) time series and defined as periods in which both HF and residual components were above their respective thresholds. Characteristic synoptic situations preceding both types of extremes were determined using the k-medoids clustering method applied on the ERA5 reanalysis data (mean sea level pressure, temperature at 850 hPa, and geopotential height of 500 hPa level). The structural similarity index measure (SSIM) was used as a distance metric. The data were divided into a training set (from the start of measurements to the beginning of 2018) and a testing set (from the beginning of 2018 to the end of 2020). For each station, the k-medoids method was used to obtain first two and then three clusters with characteristic synoptic patterns called “medoids”. Two distinct patterns related to HF and compound extremes were identified at all stations: (i) a “summer-type” pattern, characterised by a non-gradient mean sea level pressure, warm air advection from the south-southwest at 850 hPa, and the presence of a jet stream at the 500 hPa height, with all three conditions previously found to favour the development of meteorological tsunamis (i.e.  the strongest of atmospherically triggered HF sea level oscillations); (ii) a “winter-type” pattern, characterised by pronounced mean sea level pressure gradients favouring winds that induce storm surges, a colder low troposphere, and the presence of a jet stream at the 500 hPa level. Including the third cluster in the analysis led to the extraction of either a novel “bora-type” pattern, involving strong northeast winds at the Bakar and Rovinj stations, or an additional cluster with a medoid that represents the refinement of summer- or winter-type patterns. The extracted medoids of clusters were used to label all days of the testing period. It was shown that HF or compound episodes recorded in the testing period mostly appeared during synoptic situations that highly resembled extracted medoids. The potential of using the k-medoids method for forecasting HF sea level oscillations is discussed.